Portunus Weber 1795 - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
Genus Portunus Weber, 1795 Type species. Cancer pelagicus Linnaeus, 1758 [Type locality: Unknown] Remarks. The genus Portunus has been recognized as polyphyletic and accordingly a number of genera have been newly established or resurrected (Mantelatto et al. 2007; 2009; 2018; Spiridonov et al. 2014; Evans 2018; and references therein). Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 56, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155